Bank valuation & value-based management : deposit and loan pricing, performance evaluation, and risk management - Dermine, Jean. (New York : McGraw-Hill, 2009)
This book provides rigorous foundations to discuss asset and liability management at a global level, with an integrated focus on an institution's banking book. It covers bank valuation, fund transfer pricing, deposit and loan pricing, risk management, and performance measurement, and addresses two high-profile issues for banks worldwide; portfolio credit risk and liquidity risk.
Series statement from jacket.
Includes bibliographical references and index.
osa 24/05/13
Loans
Keywords: Asset-liability management; Banks and banking; Bank valuation; Value based management